Role of allopregnanolone-mediated γ-aminobutyric acid A receptor sensitivity in the pathogenesis of premenstrual dysphoric disorder: Toward precise targets for translational medicine and drug development - Gao, Qian; Sun, Wei; Wang, Yue-Rui; Li, Zi-Fa; Zhao, Feng; Geng, Xi-Wen; Xu, Kai-Yong; Chen, Dan; Liu, Kun; Xing, Ying; Liu, Wei; Wei, Sheng (Frontiers in Psychiatry, 2023)
Premenstrual dysphoric disorder (PMDD) can be conceptualized as a disorder of suboptimal sensitivity to neuroactive steroid hormones. Its core symptoms (emotional instability, irritability, depression, and anxiety) are related to the increase of stress sensitivity due to the fluctuation of hormone level in luteal phase of the menstrual cycle. In this review, we describe the emotional regulatory effect of allopregnanolone (ALLO), and summarize the relationship between ALLO and γ-aminobutyric acid A (GABAA) receptor subunits based on rodent experiments and clinical observations. A rapid decrease in ALLO reduces the sensitivity of GABAA receptor, and reduces the chloride influx, hindered the inhibitory effect of GABAergic neurons on pyramidal neurons, and then increased the excitability of pyramidal neurons, resulting in PMDD-like behavior. Finally, we discuss in depth the treatment of PMDD with targeted GABAA receptors, hoping to find a precise target for drug development and subsequent clinical application. In conclusion, PMDD pathophysiology is rooted in GABAA receptor sensitivity changes caused by rapid changes in ALLO levels. Targeting GABAA receptors may alleviate the occurrence of PMDD.